2005
DOI: 10.1074/jbc.m500463200
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor-6 Promotes Preadipocyte Differentiation through Histone Deacetylase 3-dependent Repression of DLK1

Abstract: Preadipocyte differentiation occurs during distinct periods of human development and is a key determinant of body mass. Transcriptional events underlying adipogenesis continue to emerge, but the link between chromatin remodeling of specific target loci and preadipocyte differentiation remains elusive. We have identified Krü ppel-like factor-6 (KLF6), a recently described tumor suppressor gene, as a repressor of the proto-oncogene Delta-like 1 (Dlk1), a gene encoding a transmembrane protein that inhibits adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 52 publications
3
106
1
Order By: Relevance
“…Moreover, increased serum AFP in HCC patients has been associated with histologically less differentiated state in some [39], but not all [40] studies. Similarly, in other tissues KLF6 contributes to corneal development [41], promotes adipogenesis [42], and is required for normal hematopoiesis and vasculogenesis during development [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased serum AFP in HCC patients has been associated with histologically less differentiated state in some [39], but not all [40] studies. Similarly, in other tissues KLF6 contributes to corneal development [41], promotes adipogenesis [42], and is required for normal hematopoiesis and vasculogenesis during development [43].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies aimed to map the HDAC3 region responsible for CK2 interaction would help clarifying these points. In a number of circumstances, HDAC3 is capable of establishing direct protein-protein interactions and displays biological activity independent of its recruitment in N-CoR/SMRT complexes, suggesting alternative mechanism(s) through which it can exert its transcriptional co-repression function in normal and tumor cells [94][95][96][97][98][99][100][101]. It would be tempting to speculate that HDAC3 phosphorylation might assume a critical role in activating the enzyme in N-CoR/SMRTindependent contexts.…”
Section: Ck2 Is a Key Modulator Of Class I Hdac Activitymentioning
confidence: 99%
“…In this sense, transcription factor KLF6 promotes adipogenesis by silencing the preadipocyte marker gene dlk1 through HDAC3 recruitment to the dlk1 promoter. 92 Accordingly, we have observed that the promoter region of dlk1 is acetylated in 3T3-L1 fibroblasts, when the gene is highly expressed, becoming progressively deacetylated throughout differentiation as the gene is gradually silenced. 50 On the initial phases of adipogenesis, PPARg is blocked by its association with a repressive pRb-HDAC3 complex resulting in the recruitment of deacetylase activity to PPARg target promoters and their consequent repression.…”
mentioning
confidence: 97%